(untitled) (Journal of the College of Languages (JCL), 2020)
This research focuses on shedding light on the most important criteria by which the translator can achieve total success with regard to the translation of scientific texts whose written language in Spanish is greatly influenced by expressions and words adopted from the English language and other world languages, in addition to exposing the most outstanding difficulties that translators face when translating from Spanish to Arabic, giving the most appropriate solutions in this regard. Resumen El presente trabajo de investigación se centra en echar luz sobre los criterios más importantes por los cuales el traductor puede conseguir el total éxito en la traducción de los textos científicos cuyo lenguaje escrito en español se halla influenciado a gran nivel con expresiones y palabras adoptadas de la lengua inglesa y de otras lenguas mundiales, y exponer las dificultades más destacadas que enfrentan a los traductores a la hora de traducir del idioma español al idioma árabe, dando las soluciones más adecuadas a la cabeza de las cueles llegar a un nivel aceptable de la comprensión.